CHEMICAL CHARACTERISTICS OF BRACATINGA HONEYDEW HONEY AND BLOSSON HONEY PRODUCED IN BOM RETIRO COUNTY-SC-BRAZIL (REMUNOM, 2025)
The honeys need to be characterized and identified, so that a control can be made based on its chemical characteristics and mineral content. In order to check some floral honey and honeydew honey chemical characteristics, sampling was made in ten different apiaries in two different periods of the year. The samples were tested for protein, nitrogen, ash, pH, moisture, reducing sugars, apparent sucrose, phosphorus, potassium, calcium , magnesium, sulfur, cooper, iron, manganese and zinc content. Mineral composition values varied significantly when honeydew and floral honey were compared. Honeydew honey differed from floral honey in its higher phosphorous, potassium, cooper, manganese and zinc content. The contents of reducing sugar and total reducing sugar found in floral honey were considerably higher than those found in honeydew honey.